Percepção ambiental sobre a degradação da mata ciliar em torno das margens da comunidade de rio Alto Ajuaí (Abaetetuba-PA) - SILVA, Elidiene Corrêa da (2019)
The academic paper aims to study environmental perception and the problems surrounding the riparian forest, in the community of Rio Alto Ajuaí, at the municipality of Abaetetuba – PA. As specific objectives we sought it to understand the importance of maintaining the riparian forest on the riversides to the present the problems caused by the degradation of the riparian forest and to study the causes of degradation of the riparian forest around watercourses. The reason for study on this theme was to understand what leads families to remove the riparian vegetation. The methodology used was qualitative research, followed by semi-structured interviews with questionnaires presenting open and closed questions, by means of random sampling, with the representatives of 23 families, corresponding to a sample of 10% of the total of 230 families in the community. from March to September of 2018. The results of the research prove that the degradation of the ciliary forest is related to the management of the açaí, because the ciliary species are replaced by the cultivation of the açaí, that affects in several problems as; soil erosion, water quality, the disappearance of aquatic and wild species and also in the agricultural activity itself. These problems are consequences of the way these resources are conducted, without any technical monitoring and mainly influenced by economic interest. Through this study, it was verified that the environmental impacts around the riparian forest in the community of the Rio Alto Ajuaí are due to the socioeconomic action, since the farmers knock down the trees for the açaí planting. This practice emanates from the soil erosion process cited by the families interviewed. The riparian forests are established in the Brazilian Forest Code as a Permanent Preservation Area (APP), and therefore should not be removed from their place of origin. However, it is important that the people of this community can rely on the performance of public power, having the role of providing policies aimed at raising awareness about the problem, policies to encourage the recovery of degraded areas and technical support for agricultural crop projects and extractivist species that do not interfere with the conservation of riparian forests.